L'assorbimento del glucosio in dialisi peritoneale: strumenti utili per il team multidisciplinare - Anna Laura Fantuzzi; Elisa Berri; Lida Tartaglione; Rossella Giannini; Sara Dominjanni; Silvia Porreca (AboutScience Srl, 2022)
Dialysis patients are often affected by protein energy wasting and the maintenance of an optimal nutritional state is a difficult goal to achieve. Moreover protein energy wasting is one of the strongest risk factors for mortality in chronic dialysis patients. To estimate glucose absorption in peritoneal dialysis is essential to determine patient's dietary energy requirements and to prevent possible metabolic complications. The currently accepted methods of estimating glucose absorption are two. The first one is based on the average glucose absorption of continuous ambulatory peritoneal dialysis (CAPD) and is calculated with the Grodstein et al. formula. The second one is based on the Peritoneal equilibration test curves (D/D0 formula, Bodnar et al.) and takes into account transport characteristics. None of the two formulas perfectly calculated the absolute glucose absorption, even if the D/D0 is much closer to the true value, compared to Grodstein et al. formula. In this paper we described the multidisciplinary management experience of peritoneal dialysis patients, with a focus on the estimation of the patient's energy requirements. Analyzing glucose absorption in a systematic way and monitoring the changes in glucose absorption during the time could significantly contribute to adjusting nutritional treatment. However it is always necessary to critically evaluate the results obtained by both formulas.